Gender Perspective in Determinants of Market Supply of Tomato Using Multiple Linear Regression Models - Giziew, Almaz (Journal of Agricultural Extension Management, 2018)
A clear understanding of the determinant factors of market supply in gender perspective helps policy makers. Knowing the determinants among male-headed and female-headed farmers means knowing where to focus to boost production and to improve volume supply. The estimated volume of production of tomato was about 2777.5 tons and 2759 tons of tomatoes were sold in Dugda District, Ethiopia in 2016. Sampled respondents indicated that 99.33 per cent of tomato produced was marketed and the remaining was accounted for by spoilage, seed and home consumption. Out of the total tomato marketed, 79.9 per cent and 20.1 per cent of tomato was marketed by male-headed and female-headed household heads. The multiple linear regression model results indicate that distance from the nearest market center, tomato farming experience, quantity of tomato produced, ownership of water pump, extension service, and social participation played a significant role in tomato quantity supply to the market among female-headed household heads. Family labour and quantity of tomato produced played a significant role in tomato quantity supply to the market among male-headed household heads. Therefore, policy makers should take into account determinants of quantity supplied to the market by female-headed and male-headed farmers separately for taking up appropriate interventions.